Breeding strategies for management of Tomato Leaf Curl Virus - Panchbhaiya, Ankit; Mallesh, Sanganamoni (Indian Horticulture, 2020)
Tomato is an important and most widely grown versatile vegetable crop. Several biotic stresses including the diseases caused by viruses are responsible for significant tomato production losses world over. Among the viral diseases, whitefly-transmitted geminiviruses (genus: Begomovirus) are the serious tomato production constraints in tropical and subtropical regions of the world. The disease induces severe stunting, bushy growth and partial or complete sterility depending on the stage at which infection has taken place. The disease is serious throughout India and yield losses may be as high as 100%. Several pesticides/chemicals applied against the insects failed to control the B. tabaci and attributed to the emergence of insecticidal resistance. The non-judicious use of pesticides causes environmental pollution and hazards thus increasing the cost of crop production. Varietal resistance is the best option for TLCV disease management for which various breeding methods are employed.